A Model of Technological Progress in the Microprocessor Industry1. (December 2013) - Pillai, Unni
<x xml:space="preserve">Abstract</x> This paper develops a model of technological progress in the microprocessor industry that connects the seemingly disparate engineering and economic measures of technological progress. Technological progress in the microprocessor industry is driven by the repeated adoption of higher quality vintages of capital equipment produced by the upstream semiconductor equipment industry. The model characterizes the optimal adoption decision of a microprocessor firm and the resulting rate of technological progress. In conjunction with parameters estimated using a new dataset of the microprocessor industry, the model suggests explanations for the acceleration in technological progress during 1990–2000 and the subsequent slowdown.